A eficiência da gestão da Empresa Brasileira de Serviços Hospitalares na administração do Hospital Universitário Lauro Wanderley - Lima, Valdinez da Silva (2019)
Based on the assumption that the EBSERH is a new management model of the University Hospitals, it is necessary to evaluate the management of the same, within the scope of the University Hospital Lauro Wanderley from 2013 to 2018 and if it reached levels of efficiency in the service. For that, we use as an approach the inductive method, being the research carried out of the descriptive type, with a qualitative approach. As for the technical procedures, the research was bibliographical, documentary and field. For the data collection, the chosen instruments were interview, performance evaluation indicators EBSERH / SUS to deepen the description of the characteristics of the services provided by the hospitals and questionnaire with objective and subjective questions, about the institution's organizational information and management strategies. The study population was composed of 5 (five) managers, following the organization chart of the hospital. In view of the analysis of the data, I considered that, in the managers' speeches, the objective of the EBSERH implementation achieved namely: The human resources deficit that overcome, through the 1,175 contractualizations with CLT link and use of REHUF resources for new facilities, recovery of the building, acquisition of equipment and facilities were carried out in 90%. Currently, there is a standardization of services in the EBSERH network; the organizational charts differentiated by the size of the hospitals, standardizing the actions, pointed as a positive point of the transition, as well as the implementation of an internal audit unit in the hospital. In view of the above, it concluded that within the proposed in the creation of EBSERH, it is efficient. It is suggested new research and studies on this subject so that they could continue the present research on the study object nationally in order to expand samples and detect the demands and potentialities considered relevant for the improvement of the management. At the end, a table of positive and negative management points and implementation suggestions for future analysis presented